2020
DOI: 10.1186/s40479-020-00132-8
|View full text |Cite|
|
Sign up to set email alerts
|

Living with pathological narcissism: a qualitative study

Abstract: Background: Research into the personality trait of narcissism have advanced further understanding of the pathological concomitants of grandiosity, vulnerability and interpersonal antagonism. Recent research has established some of the interpersonal impacts on others from being in a close relationship with someone having such traits of pathological narcissism, but no qualitative studies exist. Individuals with pathological narcissism express many of their difficulties of identity and emotion regulation within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 75 publications
2
19
0
Order By: Relevance
“…Not rarely treatment courses of narcissistic patients end with unpleasant surprises and sudden dropouts, fights, or an inability to end the treatment and separate from the therapist (8). Overall, our findings extend recent studies showing the interpersonal burden pathological narcissism places on relationships, both in daily life (92) and in clinical settings (93). These challenging interpersonal patterns are visible in treatment complications like drop-outs (4), the need for tact and sensitivity and therapist's adaptiveness when dealing with problematic relationship patterns (94), underlying shame (95) and the need for the therapist to turn to both fragile vulnerable aspects and provocative grandiose aspects of pathological narcissism (96).…”
Section: Theoretical Implications and Clinical Relevancesupporting
confidence: 85%
“…Not rarely treatment courses of narcissistic patients end with unpleasant surprises and sudden dropouts, fights, or an inability to end the treatment and separate from the therapist (8). Overall, our findings extend recent studies showing the interpersonal burden pathological narcissism places on relationships, both in daily life (92) and in clinical settings (93). These challenging interpersonal patterns are visible in treatment complications like drop-outs (4), the need for tact and sensitivity and therapist's adaptiveness when dealing with problematic relationship patterns (94), underlying shame (95) and the need for the therapist to turn to both fragile vulnerable aspects and provocative grandiose aspects of pathological narcissism (96).…”
Section: Theoretical Implications and Clinical Relevancesupporting
confidence: 85%
“…where skills are applied excessively). In the case of NPD, some characteristics such as excessive jealousy and paranoia (Day et al, 2020), could arise in association with over-mentalizing, rather than a reduction in social reasoning. Envy may result from the comparison between one's own and another person's mental state.…”
Section: Discussionmentioning
confidence: 99%
“…Research using measures of implicit self-esteem and implicit shame have found a relation with grandiose narcissism [ 34 , 97 , 98 ]. Moreover, informant reports of narcissism traits which partially overlap with self-reports, also highlight a dismissive yet affirmation needing stance towards others as a feature of grandiose narcissism [ 99 – 101 ]. Why those with higher grandiosity may potentially dismiss emotions such as shame and attachment anxieties requires further research, but it may be due to a self-presentation of a “false” positive self as described in the clinical literature [ 102 ].…”
Section: Discussionmentioning
confidence: 99%